Surviving Death - Johnston, M. (Mark) (Princeton : Princeton University Press, 2009)
In this extraordinary book, Mark Johnston sets out a new understanding of personal identity and the self, thereby providing a purely naturalistic account of surviving death. Death threatens our sense of the importance of goodness. The threat can be met if there is, as Socrates said, "something in death that is better for the good than for the bad." Yet, as Johnston shows, all existing theological conceptions of the afterlife are either incoherent or at odds with the workings of nature. These supernaturalist pictures of the rewards for goodness also obscure a striking consilience between the ph.
00JohnstonFM.i_xiv-revised; 01JohnstonCH01a.001_040; 02JohnstonCH01b.041_080; 03JohnstonCH01c.081_125; 04JohnstonCH02.126_188.indd; 05JohnstonCH03.189_240.indd; 06JohnstonCH04a.241_271.indd; 07JohnstonCH04b.272_304.indd; 08JohnstonCH05a.305_341; 08JohnstonCH05b.342_378; 09JohnstonINDEX. 379_394.indd.
00JohnstonFM.i_xiv-revised; 01JohnstonCH01a.001_040; 02JohnstonCH01b.041_080; 03JohnstonCH01c.081_125; 04JohnstonCH02.126_188.indd; 05JohnstonCH03.189_240.indd; 06JohnstonCH04a.241_271.indd; 07JohnstonCH04b.272_304.indd; 08JohnstonCH05a.305_341; 08JohnstonCH05b.342_378; 09JohnstonINDEX. 379_394.indd.
Print version record.
Keywords: Death; Future life; Philosophy; RELIGION -- Theology; Death; Future life; BODY, MIND & SPIRIT / Reincarnation; Electronic books; Electronic resource